2020
DOI: 10.1038/s41598-020-63463-0
|View full text |Cite
|
Sign up to set email alerts
|

Variations in cag pathogenicity island genes of Helicobacter pylori from Latin American groups may influence neoplastic progression to gastric cancer

Abstract: Helicobacter pylori (Hp) colonizes the human stomach and induces acute gastritis, peptic ulcer disease, atrophic gastritis, and gastric adenocarcinoma. increased virulence in Hp isolates derives from harboring the cag (cytotoxin-associated genes) pathogenicity island (cagpAi). We analyzed the microvariants in cagpAi genes with the hypothesis that they may play an important role in determining Hp virulence. We tested DnAs from cagA positive patients HP isolates; a total of 74 patients with chronic gastritis (cG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
1
15
0
2
Order By: Relevance
“…Finally, we also removed 46 subjects with duodenal ulcer, leaving a total number of 1220 samples for analysis. We checked that allelic frequencies of all polymorphisms were in general agreement with those observed in the sequencing analysis reported in our previous work 13 …”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…Finally, we also removed 46 subjects with duodenal ulcer, leaving a total number of 1220 samples for analysis. We checked that allelic frequencies of all polymorphisms were in general agreement with those observed in the sequencing analysis reported in our previous work 13 …”
Section: Methodssupporting
confidence: 66%
“…Additionally, this work did not include large structural variations. However, we studied EPIYA and CM motifs in our sequencing study and we did not observe any association with risk of IM and/or GC 13 . Moreover, structural variations are meaningfully studied only by sequencing, which most of our samples are unsuitable for.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Los resultados obtenidos muestran una asociación entre el polimorfismo de interleucina IL-1β+3954(C>T) y el cáncer gástrico. Ya que diversos estudios han identificado y relacionado con un incremento en la producción de la interleucina frente a patógenos, ya que es una molécula proinflamatoria importante en la señalización y amplificación de la respuesta frente a la infección por Helicobacter pylori, produciendo un proceso inflamatorio que puede desencadenar la transformación maligna de la mucosa, a través de cambios moleculares y morfológicos (21,22 (24). En el análisis estadístico de Odds ratio, los valores de OR con IC 95% se calcularon con respecto al homocigoto normal de cada polimorfismo estudiado.…”
Section: Discussionunclassified
“…In a recent study, polymorphisms on the nucleotide level in cagA , such as cagA 1283 and cagA 2551, have been associated with high-grade premalignant lesions, and the polymorphisms such as cagA 2419 and cagA 3435 together with polymorphism in cagL , such as cagL 400, have been associated with the risk of gastric cancer development [ 30 ]. Moreover, amino acid variations in CagA such as V52I, S194F, and Q/R427K have been associated with the risk of intestinal metaplasia, whereas N467G has been associated with the development of gastric cancer [ 31 ]. The studies have found the development of gastric cancer only in 1–2% of H. pylori -infected individuals and MALT lymphoma in even less than 0.1% of individuals [ 32 , 33 ].…”
Section: Cytotoxin-associated Gene a (Caga)mentioning
confidence: 99%